The mechanistic implications of the high temperature, long time thermal stability of nanoscale Mn-Ni-Si precipitates in irradiated reactor pressure vessel steels. (May 2020) - Almirall, N.; Wells, P.B.; Pal, S.; Edmondson, P.D.; Yamamoto, T.; Murakami, K.; Odette, G.R.
Abstract: Post irradiation annealing (PIA) clarified the induced versus enhanced controversy regarding nanoscale Mn-Ni-Si precipitate (MNSP) formation in pressure vessel steels. Radiation induced MNSPs would dissolve under high temperature PIA, while radiation enhanced precipitates would be stable above a critical radius (rc ). A Cu-free, high Ni steel was irradiated with 2.8MeV Fe 2+ ions at two temperatures to generate MNSPs with average radii ( r ¯ ) above and below an estimated rc for PIA at 425  °C up to 52 weeks. Atom probe tomography and energy dispersive x-ray spectroscopy showed MNSPs with r  < rc dissolved, while those with r  > rc slightly coarsened, consistent with thermodynamic predictions. Graphical abstract: Image, graphical abstract